1982
DOI: 10.1073/pnas.79.20.6166
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid sequence homology among the 2-hydroxy acid dehydrogenases: mitochondrial and cytoplasmic malate dehydrogenases form a homologous system with lactate dehydrogenase.

Abstract: The amino acid sequence of porcine heart mitochondrial malate dehydrogenase (mMDH; L-malate:NAD+ oxidoreductase, EC 1.1.1.37) has been compared with the sequences of six different lactate dehydrogenases (LDH; Llactate:NAD' oxidoreductase, EC 1.1.1.27) and with the "x-ray" sequence of cytoplasmic.malate dehydrogenase (sMDH). The main points are that (i) all three enzymes are homologous; (ii) invariant residues in the catalytic center of these enzymes include a histidine and an internally located aspartate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 27 publications
4
83
0
Order By: Relevance
“…The plMDH forms also contain a group of conserved residues (IWGNH) near the active site histidine (Metzler et al, 1989). This same motif can be found in lactate dehydrogenases and cMDH forms from alfalfa and mouse (Birktoft et al, 1982;Metzler et al, 1989). The maize plMDH also contains a consensus sequence of CFGVFC that has been shown to be the site of thioredoxin regulation of the isoform (Hatch and Slack, 1969).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The plMDH forms also contain a group of conserved residues (IWGNH) near the active site histidine (Metzler et al, 1989). This same motif can be found in lactate dehydrogenases and cMDH forms from alfalfa and mouse (Birktoft et al, 1982;Metzler et al, 1989). The maize plMDH also contains a consensus sequence of CFGVFC that has been shown to be the site of thioredoxin regulation of the isoform (Hatch and Slack, 1969).…”
Section: Discussionmentioning
confidence: 82%
“…Several MDH cDNA clones have been isolated and sequences compared from both plant (Cretin et al, 1988;Gietl, 1992;Guex et al, 1995;Kim and Smith, 1994;Metzler et al, 1989) and animal sources (Birktoft et al, 1982;Grant et al, 1986;Joh et al, 1987a;Joh et al, 1987b). The sequences of both the mouse and yeast c-and mMDH genes have been reported (Minard and McAlister-Henn, 1991;Setoyama et al, 1988;Takeshima et al, 1988;Thompson et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…1) for mMDH-FITC conjugates prepared using protocol P, a Po value for fluorescein of 0.47 (Hamman et al, 1996) and the observed lifetime of 4.16 ns, the calculated rotational relaxation time calculated is 25 ns. The Debye rotational relaxation time expected for a rigid, spherical 68 kDa protein, in aqueous buffer at 20 "C (77 = 1 .OO cp), assuming a partial specific volume of 0.75 mL/g [calculated from the amino acid sequence (Birktoft et al, 1982) using the method of Cohn and Edsall (1943)] and a hydration of 0.22 mL/g, is 74 ns. Clearly, the experimentally determined rotational relaxation time is significantly shorter than that expected for a 68 kDa spherical protein, and we may presume that the probe is monitoring more than one rotational motion.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of the optimum pH for m-MDH activity in the oxaloacetate reductase direction was performed with 200 lM oxaloacetate and 200 lM NADH over a wide pH range (4)(5)(6)(7)(8)(9)(10)(11)(12) and at 30°C. Determination of the pH optimum in the malate oxidation direction was achieved with 10 mM malate and 1 mM NAD + as substrate and cosubstrate, respectively, over the same pH range at 30°C.…”
Section: Determination Of Selected Biochemical Propertiesmentioning
confidence: 99%